Clinical Outcomes of Single-Level Anterior Cervical Discectomy and Fusion - NIEDERMEIER, STEVEN R. (Int J Spine Surg, 2018)
BACKGROUND: The purpose of the present study was to determine the differences in health outcomes between patients with cervical spondylosis who underwent single-level anterior cervical discectomy and fusion (ACDF) and patients with cervical spondylosis who did not undergo an ACDF fusion (non-ACDF). The hypothesis of the study was that patients undergoing single-level fusion have a lower risk of downstream cardiovascular disease and depression. METHODS: The Medicare 5% sample was used to identify patients who received a diagnosis of spondylosis during 2005–2012. All spondylosis patients were separated into nonoperative and operative groups. Differences in new disease diagnoses, age, sex, and Charlson Comorbidity Index (CCI) scores were recorded. RESULTS: The relative risk (RR) of heart failure was lower in the ACDF group after 3 years (RR = 0.6719; P < .05), 5 years (RR = 0.8477; P = 1.17), and 7 years (RR = 0.7709; P = 1.625). The RR of depression was higher in the ACDF group at 1 year (RR = 2.5008), 3 years (RR = 1.4473), 5 years (RR = 2.2625), and 7 years (RR = 2.2257; P < .05 for all). Mean CCI score of patients before undergoing ACDF was 10 (SD, 9.20), whereas the mean score after surgery was 8 (SD, 7.84; P < .05), and the score for non-ACDF patients remained unchanged at a CCI of 10 (SD, 9.00; P < .05). CONCLUSIONS: The results demonstrate the patients in the ACDF cohort have an increased RR of depression but a decreased risk of cardiovascular disease. Further research may be needed to delineate why the ACDF procedure potentially benefits a patient for heart disease but may stress a patient's social/economic supports during the recovery process, thus leading to higher depression rates for patients undergoing ACDF.